Pelatihan Kewirusahaan Berbasis Internet : Tips dan Trik Sukses Berbisnis Online Bagi Remaja Milenial di Desa Kaduara Barat Pamekasan - Aflahah Aflahah; Mohammad Imam Sufiyanto (IAIN Madura, 2019)
The way to maximize the potential of youth entrepreneurial spirit is through the internet-based entrepreneurship training program